The effect of acute vibration exercise on short-distance sprinting and reactive agility - Cochrane, D. J. (Journal of Sports Science & Medicine, 2013)
Vibration exercise (VbX) has been a popular modality to enhancing physical performance, where various training methods and techniques have been employed to improve immediate and long-term sprint performance. However, the use of acute side-alternating VbX on sprint and agility performance remains unclear. Eight female athletes preformed side-alternating vibration exercise (VbX) and control (no VbX) in a cross over randomised design that was conducted one week apart. After performing a warm-up, the athletes undertook maximal 5m sprints and maximal reactive agility sprints (RAT), this was followed by side-alternating VbX (26 Hz, 6mm) or control (no VbX). Immediately following the intervention, post-sprint tests and RAT were performed. There was a significant treatment effect but there was no time effect (pre vs. post) or interaction effect for sprint and RAT; however, side-alternating VbX did not compromise sprint and agility performance.